Evaluation of ocular surface and tear film function following modified Hughes tarsoconjunctival flap procedure. (7th March 2013) - Klein‐Theyer, Angelika; Horwath‐Winter, Jutta; Rabensteiner Dieter, Franz; Haller‐Schober, Eva‐Maria; Riedl, Regina; Boldin, Ingrid
Abstract. Purpose: To evaluate ocular surface characteristics and tear film function following modified Hughes flap for eyelid reconstruction. Methods: This is an institutional study including 18 patients (6 male, 12 female) who underwent a tarsoconjunctival flap for reconstructing the lower eyelid's posterior lamella in one eye between 2005 and 2010. The median age of the patients was 72 (49–93) years at the time of surgery and 77 (51–97) years at the time of evaluation. The median follow‐up time was 34 (9–69) months. All patients had large malignant or semi‐malignant lid tumours. Data for subjective symptoms (OSDI questionnaire), lid margin morphology, tear break‐up time (BUT), vital staining, Schirmer test, impression cytology, tear film osmolarity, lipid layer interference patterns, meibography and the size of the tumour and flap were recorded and compared with the contralateral side. Results: Statistical analysis of the data revealed a significant difference between the surgically treated lid and the untreated side in meibomian gland loss, more lid margin abnormalities in the upper and lower eyelid (p < 0.001) and increased fluorescein staining of the cornea (p = 0.031). For the operated side, the median OSDI score was higher (17.2 versus 14.7), and the median BUT value was shorter (4.2 versus 5.6 seconds) compared with the median values of the contralateral side. Conclusion: Despite the favourable cosmetic and functional results of the Hughes tarsoconjunctival flap, our results indicate that this procedure does affect the ocular surface health in the treated eyes.